The Ghost Story of Kuyang: Establishing Social Construction of Belief System on Identity in Kalimantan - Suprianto, Bibi; Kurniawan, Syamsul; Riyani, Riyani (Mimbar Agama Budaya, 2024)
This research described the social construction of the belief system on the identity of the ghost Kuyang in Kalimantan. This research argues that ghost stories have constructed the ghost's identity of gender and place. The gender always represents the ghost as a woman while the place represents the Kuyang ghost as a Dayak or Malay tribe in Kalimantan. This research formulates how the Kuyang ghost story can establish a social construction of the belief system on identity in Kalimantan. This research uses a descriptive qualitative method by collecting data through storytelling in the community and on YouTube social media. The results of this study show that: 1) female ghost stories represent a patriarchal system for women; 2) the development of a belief system in local communities; 3) community responses through tradition and religion; and 4) social construction shapes the identity of Ghost Kuyang in Kalimantan. The development of the social construction of the belief system in the ghost of Kuyang can bring a new discourse on identity following ethnic, religious, and culture in Kalimantan.